2022
DOI: 10.29303/jipp.v7i2b.524
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Motivasi Belajar dengan Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas IV SDN 3 Gunungsari Tahun Ajaran 2021/2022

Abstract: Motivasi belajar merupakan daya dorong utama umum pada siswa yang melahirkan latihan-latihan pembelajaran, yang menjamin kemajuan latihan-latihan pembelajaran dan memberikan bimbingan kepada latihan-latihan pembelajaran, sehingga tujuan yang diinginkan oleh mata pelajaran pembelajaran dapat tercapai. Hasil belajar dapat diartikan sebagai tingkat kemajuan siswa dalam memperoleh topik yang dikomunikasikan dalam skor yang diperoleh dari hasil tes terhadap berbagai topik. Terlebih lagi, Ilmu Sosial Sosial (IPS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
2
Order By: Relevance
“…This finding is in line with the results of the study which showed there was a significant positive relationship between the learning environment and learning achievement P=0.000. A supportive learning environment will create a conducive atmosphere that supports students to learn well so that it is expected to make it easier for students to achieve learning success (Rahmawati, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the results of the study which showed there was a significant positive relationship between the learning environment and learning achievement P=0.000. A supportive learning environment will create a conducive atmosphere that supports students to learn well so that it is expected to make it easier for students to achieve learning success (Rahmawati, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Sari, lembaga pendidikan ( sekolah ) merupakan suatu wadah bagi para siswa dalam mendapatkan atau menggali ilmu pengetahuan. Faktor yang dapat mempengaruhi tingkat hasil belajar adalah faktor internal dan faktor eksternal [7]. Dimana Faktor internal merupakan faktor yang bersumber dari dalam diri peserta didik (siswa) yang mempengaruhi kemampuan belajarnya.…”
Section: Pendahuluanunclassified
“…A person who finds calm and self-confidence must want and be self-motivated. According to Rachmawati & Amin (2014) that learning motivation contributes to student learning outcomes in class IV social studies subjects.…”
Section: Correlation Of Learning Motivation (X1) With Student Learnin...mentioning
confidence: 99%